Strategi Penerapan Metode Mind Mapping dalam Penguasaan Mufrodat Bahasa Arab : (Studi Kasus di Madrasah Ibtidaiyah Almaarif 05 Singosari) - Nurul Khikmatul ilmiah; Humaidi Humaidi (Qismul Arab: Journal of Arabic Education, 2023)
Mastery of mufrodat is one of the keys in language learning, especially Arabic, mufrodat is the beginning of students' knowledge in speaking, writing, listening and even reading. However, if the method used in learning mufrodat is not varied, it tends not to create effective learning. So in this study I offer a new method for mastering mufrodat, namely the mind mapping method in mastering Arabic mufrodat. The purpose is to find out the application of mind mapping strategy in learning Arabic and to find out the results of learning mufrodat through mind mapping strategy. This research method is a qualitative descriptive approach by means of observation, interviews with teachers and students, and documentation at Madrasah Ibtidaiyyah Islamiyah Pakis -Malang in the 2022/2023 academic year. The results of this study are first: The teacher distributes manila paper. Students write and draw according to the theme that has been distributed by the teacher. Students decorate it as creatively as possible with color pens so that the results of mind mapping look more attractive. Then students present the results in front of the class. Second, increasing students' Arabic vocabulary, and memorizing vocabulary quickly with the help of pictures.